Language as a tool for the oppression of women in marriages in the Shona society: A critical discourse analysis approach - Mukaro, Juliet; Mapfunde, Davie; Mzizi, Lynn (ARKA INSTITUTE, 2025)
This qualitative research is a Critical Discourse Analysis of the ways in which language is used by people in the Shona society when giving women marital advices. It specifically identifies harmful Shona phrases used when advising women on marital issues, examines how the phrases reinforce the oppression of women in the Shona society and the repercussions of using such phrases on women. Results of the research indicate that the phrases used when giving women marital advice reinforce the oppression of women as they limit women’s access to education and economic opportunities, perpetuate gender stereotyping, victim blaming, emotional blackmail, sexism and misogyny, male dominance and gendered expectations. Findings reflect that using these phrases on women make them give up on their educational goals, tolerate and normalise abusive behaviours and hang in abusive marriages which is detrimental to their physical and emotional health. Results help raise awareness among policy makers about the sources of gender oppression and inequality as gender equality is a topical issue within Zimbabwe and the world over. Results also raise awareness among people about how the language they use when advising each other on marital issues can reinforce systems of oppression, patriarchal beliefs, gender inequality and intolerance.